Peer Tutoring as a Collaborative Approach in Arabic Language Learning - Nur Hanifansyah; Mahmudah, Menik; Syakur, Sultan Abdus (Program Studi Pendidikan Bahasa Arab, 2024)
In an era where traditional teaching methods often fail to meet the evolving needs of language learners, peer tutoring emerges as a transformative approach to Arabic language education. This study explores peer tutoring as a collaborative strategy at Darullughah Wadda’wah Islamic Boarding School (pesantren), addressing challenges such as limited class time, imbalanced teacher-student ratios, and rigid instructional methodologies. Using a qualitative case study design, data were collected through classroom observations, interviews, focus group discussions, and document analysis involving 30 students (15 tutors and 15 tutees) and 3 Arabic teachers. Findings reveal significant improvements in classroom dynamics, motivation, and confidence. Tutors developed leadership skills and reinforced their knowledge through the learning-by-teaching phenomenon, while tutees received personalized support, reducing anxiety and enhancing engagement. Despite challenges such as proficiency gaps, reliance on rote memorization, and the need for teacher supervision, peer tutoring fostered teamwork, critical thinking, and self-directed learning habits. This study concludes that peer tutoring transcends its role as a mere instructional method, acting as a catalyst for holistic academic excellence and personal empowerment. Recommendations include systematic implementation frameworks to balance academic rigor with social-emotional development, ensuring sustainable improvements in Arabic language education within Islamic boarding schools.